Renal recovery after acute kidney injury - Forni, L. G.; Darmon, M.; Ostermann, M.; Oudemans-van Straaten, H. M.; Pettilä, V.; Prowle, J. R.; Schetz, M.; Joannidis, M. (Intensive care medicine, 2017)
Acute kidney injury (AKI) is a frequent complication of critical illness and carries a significant risk of short- and long-term mortality, chronic kidney disease (CKD) and cardiovascular events. The degree of renal recovery from AKI may substantially affect these long-term endpoints. Therefore maximising recovery of renal function should be the goal of any AKI prevention and treatment strategy. Defining renal recovery is far from straightforward due in part to the limitations of the tests available to assess renal function. Here, we discuss common pitfalls in the evaluation of renal recovery and provide suggestions for improved assessment in the future. We review the epidemiology of renal recovery and of the association between AKI and the development of CKD. Finally, we stress the importance of post-discharge follow-up of AKI patients and make suggestions for its incorporation into clinical practice. Summary key points are that risk factors for non-recovery of AKI are age, CKD, comorbidity, higher severity of AKI and acute disease scores. Second, AKI and CKD are mutually related and seem to have a common denominator. Third, despite its limitations full recovery of AKI may best be defined as the absence of AKI criteria, and partial recovery as a fall in AKI stage. Fourth, after an episode of AKI, serial follow-up measurements of serum creatinine and proteinuria are warranted to diagnose renal impairment and prevent further progression. Measures to promote recovery are similar to those preventing renal harm. Specific interventions promoting repair are still experimental.